Comprehensive Laboratory Evaluation of Recycling Agent Treated Plant-Produced Asphalt Mixtures. Issue 9 (September 2022) - Zhang, Runhua; Sias, Jo; Dave, Eshan; Hanz, Andrew; Reinke, Gerald; Wang, Zheng
Recycling agent (RA) is typically used to restore or rejuvenate the properties of aged asphalt to desired properties. This study was motivated to comprehensively characterize the performance of asphalt mixtures treated with RA. The overarching goal of the research project is to provide guidance to agencies for revising asphalt mixture specifications to include RAs. Ten plant-produced mixtures were evaluated including three control mixtures (with 30 and 40% reclaimed asphalt pavement [RAP]) and seven 40% RAP mixtures treated with different RA products. Mixture testing was conducted with and without laboratory conditioning of loose mixture for 6 h at 135°C. Testing included the mixture Complex Modulus (E*) test for viscoelastic characterization, Direct Tension Cyclic Fatigue test for fatigue performance evaluation, Tensile Strength Ratio test for moisture susceptibility evaluation, and Semi-circular Bending test, Cracking Index Test and Disk-shaped Compact Tension test for mixture cracking and fracture behavior at different temperatures. In addition, the Hamburg Wheel Track Testing was conducted for rutting performance characterization on the unaged mixtures. Results show that addition of different RAs can improve the properties of asphalt mixtures by softening the mixtures with RAP and improving the cracking performance as compared with the control mixtures. However, addition of RA could severely deteriorate the rutting performance of mixtures and increase the moisture susceptibility as compared with the control mixtures. In addition, addition of certain RAs can also decrease the aging resistance of asphalt mixtures, specifically in context of cracking performance.